The Heart-Shaped Sign Infarct: A Rare Case of Bilateral Medial Medullary Infarction - Japutri, Josephine; Puspitasari , Vivien (Acta Neurologica Indonesia, 2025)
Introduction Medullary infarction is a life-threatening condition with an incidence rate of 0.5-1.5% of all ischemic strokes. It seldom occurs bilaterally and might cause fatal respiratory complications. Here, we present a rare case of Bilateral Medial Medullary Infarct (BMMI) with unique Magnetic Resonance Imaging (MRI) findings and discuss its anatomical involvement. Case Report a 67-year-old man with poorly controlled hypertension and diabetes presented with acute visual impairment, dysphagia, dysarthria, and left hemiparesis since one day before. On the third day post-stroke, the patient developed quadriparesis along with worsening bulbar symptoms. Brain MRI revealed a heart-shaped infarct in the medial medulla, confirming the rare diagnosis of BMMI. The patient was treated with antiplatelet, and there were no further complications. Discussion Although rare, clinical findings of bulbar symptoms, quadriparesis, and respiratory involvement may aid early identification of BMMI. Brain MRI is recommended as they reveal the radiological hallmark of a heart-shaped infarct associated with the anteromedial and anterolateral branch of the vertebrobasilar artery that suplies the medullary. MRI is useful in differentiating BMMI from other neurological disorders and determining proper course of treatment. Conclusion BMMI early identification with a typical heart-shaped infarct is essential to prevent fatal respiratory failure. Risk factors management is crucial to prevent recurring infarcts.